PSEUDOTACHYLITE FROM McINTYRE ISLAND, ENDERBYLAND, EAST ANTARCTICA : EVIDENCE FOR A RAPID CRYSTALLIZATION - モトヨシ, ヨウイチ; MOTOYOSHI, Yoichi (National Institute of Polar Research, 1996)
P(論文) Pseudotachylite from McIntyre Island in Enderby Land, East Antarctica, occurs in a breccia zone composed of black material with glassy luster and fragments of host pyroxene gneiss which has undergone ultra-high temperature metamorphism as a constituent of the Archean Napier Complex. Under the optical and electron microscopes, the rock in the zone demonstrates a distinct sheared texture with extremely fine-grained materials, a part of which may be a glass. Abundant euhedral garnets occur in the fine-grained part, and their chemical compositions are quite heterogeneous from domain to domain. In view of the evidence that no garnet was observed in the host pyroxene gneiss, these garnets are likely to have crystallized very rapidly in the melt or solidified melt. Because of the chemical heterogeneity of garnet in the pseudotachylite even in a small domain, it is highly difficult to estimate the P-T conditions by means of geothermobarometric techniques using the mineral chemistries of microlites. departmental bulletin paper